2023
DOI: 10.1002/mp.16265
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arteries segmentation from CT images using PA‐Net with attention module and contour loss

Abstract: Background: Pulmonary embolism is a kind of cardiovascular disease that threatens human life and health. Since pulmonary embolism exists in the pulmonary artery, improving the segmentation accuracy of pulmonary artery is the key to the diagnosis of pulmonary embolism. Traditional medical image segmentation methods have limited effectiveness in pulmonary artery segmentation. In recent years, deep learning methods have been gradually adopted to solve complex problems in the field of medical image segmentation.Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In addition, it was reported that without using contrast media, contouring the borders between the structures can be difficult ( 11 ). Furthermore, using only CT axial slices to train the model can produce lower segmentation quality ( 5 ). Image resolution can affect the segmentation quality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it was reported that without using contrast media, contouring the borders between the structures can be difficult ( 11 ). Furthermore, using only CT axial slices to train the model can produce lower segmentation quality ( 5 ). Image resolution can affect the segmentation quality.…”
Section: Discussionmentioning
confidence: 99%
“…Training the model with different CT acquisitions for instance CT images with and without contrast media can enhance the DSC scores ( 11 ). Moreover, training the model with three CT planes (axial, sagittal, and coronal) might improve the segmentation's quality ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Next we compare the CTV delineation quality of several DL models, including the proposed PPAF-net, PPF-net, the RA-CTVNet, 23 model by Rhee et al, 20 U-Net, 24 U-Net++, 25 EANet, 44 DeepLab v3+, 22 MSRF-Net, 45 TransUNet, 46 SegFormer, 47 SETR, 48 PA-Net 49 and OAU-Net. 50 The PPF-net is the PPAF-net without the attention module.…”
Section: Performance Evaluationmentioning
confidence: 99%